NRF2 modulates WNT signaling pathway to enhance photodynamic therapy resistance in oral leukoplakia - Tiantian Xu; Liang Zhong; Qianxi Liu; Fei Wang; Wenjing Kuang; Jiaqi Liang; Dan Yang; Xikun Zhou; Hongxia Dan; Hang Zhao; Taiwen Li; Xin Zeng; et al. (EMBO Molecular Medicine)
Abstract Oral leukoplakia (OLK) is a common potentially malignant oral disorder with high risk of malignant transformation. While photodynamic therapy (PDT) offers a minimally invasive treatment for OLK, some patients show resistance to PDT and the mechanisms remain unclear. This study aims to identify key regulatory pathways driving PDT resistance in OLK. Single-cell RNA sequencing of OLK samples (three PDT-sensitive, three PDT-resistant) revealed significant NRF2 upregulation in resistant tissues. Validation across two independent cohorts (n = 117) confirmed that p-NRF2 levels were significantly elevated in PDT-resistant cases, exhibiting strong predictive power for treatment response (AUC > 0.8). Mechanistically, NRF2 promotes CTNNB1 transcription, activates WNT signaling, modulates reactive oxygen species responses, and regulates keratinization, collectively contributing to PDT resistance. In a 4NQO-induced OLK mouse model, NRF2 inhibition combined with PDT effectively reversed OLK lesions and restored mucosal histology. These findings establish p-NRF2 as a valuable biomarker for guiding PDT regimens in OLK patients, reveal NRF2’s role in mediating PDT resistance via the WNT signaling pathway, and highlight NRF2 inhibition as a promising strategy to enhance PDT efficacy.